2016
DOI: 10.3847/2041-8205/820/1/l13
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitous Presence of Looplike Fine Structure Inside Solar Active Regions

Abstract: Although most of the solar surface outside active regions (ARs) is pervaded by small-scale fields of mixed polarity, this magnetic "carpet" or "junkyard" is thought to be largely absent inside AR plages and strong network. However, using extreme-ultraviolet images and line-of-sight magnetograms from the Solar Dynamics Observatory, we find that unipolar flux concentrations, both inside and outside ARs, often have small, loop-shaped Fe IX 17.1 and Fe XII 19.3 nm features embedded within them, even though no mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 21 publications
3
23
1
Order By: Relevance
“…We note further that similar energetic events at the feet of coronal loops could possibly create jet-like structures observed at these locations (Chitta et al 2017a,b). In addition, given the increasing evidence for the presence of unresolved minority polarities in the photosphere (e.g., Solanki et al 2017;Smitha et al 2017), such ejections resulting from flux cancellation can give rise to jet-like features found inside plages and strong network associated with the unresolved underlying minority polarities (Wang 2016;Wang et al 2019). We expect that other small-scale phenomena, such as spicules, could be associated with reconnection at lower atmospheric heights between converging cancelling polarities, and can potentially be associated with the cool outflows predicted from our model for different values of parameter space (e.g., Samanta et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We note further that similar energetic events at the feet of coronal loops could possibly create jet-like structures observed at these locations (Chitta et al 2017a,b). In addition, given the increasing evidence for the presence of unresolved minority polarities in the photosphere (e.g., Solanki et al 2017;Smitha et al 2017), such ejections resulting from flux cancellation can give rise to jet-like features found inside plages and strong network associated with the unresolved underlying minority polarities (Wang 2016;Wang et al 2019). We expect that other small-scale phenomena, such as spicules, could be associated with reconnection at lower atmospheric heights between converging cancelling polarities, and can potentially be associated with the cool outflows predicted from our model for different values of parameter space (e.g., Samanta et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While the spatial resolution of the coronal images of Hi-C is about 0.3 (and thus more than three times better than AIA), the conclusions of Peter et al (2013) had to rely on the comparably poor resolution of HMI, too. In addition, Wang (2016) showed one example where a loop-like structure is found at the footpoint of a loop with the general appearance of an inverse Y. So there is evidence for a complex magnetic nature of unipolar-looking regions.…”
Section: Introductionmentioning
confidence: 99%
“…He showed that there are small coronal loopshaped features with horizontal sizes of only 5 Mm that are embedded in the same seemingly unipolar magnetic field region in a plage area. From this Wang (2016) concluded that there must be small-scale opposite magnetic polarities embedded within the plage region that appears to be unipolar to HMI with its limited spatial resolution of no better than 1 (corresponding to 725 km on the Sun at disk center). This is similar to the interpretation given earlier by Peter et al (2013) for even smaller loop-like features with lengths of only 1 Mm seen with the High-resolution Coronal Imager (Hi-C; Kobayashi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until very recently magnetic field measurements were dominated by SOHO/MDI, SDO/HMI, and Hinode/SOT instruments and several studies based on these data (e.g., Del Zanna 2003;Ugarte-Urra et al 2009) reported that coronal loops are often connected to highly dynamic but nevertheless unipolar plage fields. However, recently Wang (2016) argued that HMI instrument does not resolve many small-scale structures so, that mixed polarity may be present Using a similar approach Tiwari et al (2017) also argued that coronal heating may be fueled by vigorous magneto-convection which can braid magnetic field lines and that the heating rate is directly dependent on the field strength in the loop. However, strong fields, such as those found in the sunspot umbra suppress magnetoconvection thus reducing the heating rate (e.g., Chen et al 2014;Tiwari et al 2017).…”
Section: Summary and Discussionmentioning
confidence: 99%